Exam credits and exam performance in university economics courses − evidence from a regression discontinuity experiment. Issue 9 (20th May 2020) - Katare, Bhagyashree; Chen, Qihui; Wetzstein, Michael
ABSTRACT: We estimate effects of nonfinancial incentives, combined with the notion of 'loss aversion, ' on students' exam performance in two introductory economics courses. Our experiment awarded five points to students who scored below the median score on Midterm I as an incentive to improve their performance on Midterm II − these points would be lost if they failed to improve their performance. Regression discontinuity analysis indicates that this incentive improved male students' performance by 0.38 standard deviations on Midterm II.